Verbal Forms In Specialized Written Discourse - Dimković-Telebaković Gordana (Romanian Journal of English Studies, 2012)
The frequency and the distribution of verbal forms are analyzed in eleven professional texts for six fields of transport and traffic engineering, in a corpus of 7,215 lexemes. The analysis shows that passive forms, for example, occur far less than active forms. Certain functions and meanings of the most frequently used verbal forms are then discussed.